A statistical analysis of Norges Bank's forecasts - Kåre Hagelund; Eilert Husabø (Norges Bank, 2022)
In this paper, we perform a statistical analysis of the forecasting properties of Norges Bank's macroeconomic forecasts in the period 1998 - 2019. As a part of the analysis we assess Norges Bank's forecasts against similar forecasts by Statistics Norway and forecasts from simple models. The review shows that Norges Bank's projections have stood up well compared with Statistics Norway's projections and have generally been better than forecasts from simple models, especially in the short run. The projections were for the most part unbiased, but for wages and CPI inflation adjusted for tax changes and excluding energy prices (CPI-ATE), the projections were too high one and two years ahead. The productivity growth projections were too high at all horizons. Exchange rate projections based on "random walk" models were better than Norges Bank's projections.
hdl:11250/2997513
Keywords: 330; Forecasts; forecasting properties; evaluation